2012
DOI: 10.1177/0960327112440113
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and resveratrol in combination modulates benzo(a)pyrene-induced genotoxicity during lung carcinogenesis

Abstract: The present study attempted to explore the efficacy of curcumin and resveratrol in modulating mitotic catastrophe and apoptosis during lung carcinogenesis. The mice were segregated into five groups, which included normal control, benzo(a)pyrene (BP)-treated, BP + curcumin (C)-treated, BP + resveratrol (R)-treated and BP + C + R-treated groups. The BP treatment resulted in a significant increase in the formation of micronuclei as well as in the protein expression of bcl-2 in the lungs of mice. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…7 The Synergistic potential of curcumin and resveratrol in declining the active tumour suppressor protein in the lungs of Benzo[a]pyrene treated mice were reported earlier. 8 In vitro cell line study and in vivo study in mice for prostatic adenocarcinoma using curcumin and resveratrol drug combination induced apoptosis and decreased cell growth. 9 Enhancement of curcumin activity in the presence of resveratrol is reported against head and neck carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…7 The Synergistic potential of curcumin and resveratrol in declining the active tumour suppressor protein in the lungs of Benzo[a]pyrene treated mice were reported earlier. 8 In vitro cell line study and in vivo study in mice for prostatic adenocarcinoma using curcumin and resveratrol drug combination induced apoptosis and decreased cell growth. 9 Enhancement of curcumin activity in the presence of resveratrol is reported against head and neck carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports where combinatorial effect of dietary anticancer agents against lung and liver carcinoma was explored (Malhotra et al, 2012;Du et al, 2013). In the context of breast cancer, it has already been demonstrated that combination of two or more drugs has an improved molecular action against different types and stages of breast cancers (Kim et al, 2013;Nasiri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals are non nutritive products of plants and are presently being studied the world over for their chemopreventive actions in controlling various diseases including cancer. Amongst various chemo-preventive agents, phytochemicals especially curcumin and resveratrol in combination have shown great potential in combating cancer as observed in our previous studies [5][9]. However, there is paucity of information with regard to molecular mechanics behind these synergistic effects of curcumin and resveratrol.…”
Section: Introductionmentioning
confidence: 90%